Employee’s perception on merger between Proton Holdings Berhad and Geely on talent management practices / Nor Afiqah Mohd Sofian, Nurul Huda Roslan and Wan Mohd Khairul Naim Mohd @ Wan Mohamad - Mohd Sofian, Nor Afiqah; Roslan, Nurul Huda; Mohd @ Wan Mohamad, Wan Mohd Khairul Naim (Arshad Ayub Graduate Business School, 2018)
Proton Holding Berhad experiencing critical challenges in dealing with negative perception of employees after merger with Geely on talent management practices. The increasing of absenteeism and brain drain of Proton employees was alarming and worsened over the year. This has led to decreasing of revenue and employees’ performance. As such, the study examines employees’ overall perception after the merger between Proton Holdings Berhad (Proton) with Geely on talent management practices. The study investigate d the differences perception by gender, academic qualification, working experience and employees’ level on talent management practices encompassing job design, compensation, performance management, learning and development and career development after the merger between Proton and Geely. The instrument used to gather the data was a modified questionnaire distributed to 250 respondents using simple random sampling. Besides that, an unstructured interview was conducted with the Human Resource Manager of Proton. The research used IBM SPSS Statistics Version 21. By using the descriptive and inferential statistic technique, the result showed that all five dimensions of talent management practices namely job design, compensation, performance management, learning and development and career development had a significant moderate level of satisfaction to the employees after the merger. Therefore, it is recommended for Proton to focus on job design, compensation, performance management, learning and development and career development in order to ensure their sustainability and competitive advantage in the automotive industry. However, the limitation of this study was that there were limited sources of information from the data and the accessibility to get the data as data was treated as confidential. Also, the study focused only on the plant in Tanjung Malim.